2024
DOI: 10.3389/fphys.2024.1359476
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, weight maintenance, and nonalcoholic fatty liver disease risk: a Chinese cohort study

Chao Yang,
Peijing Yan,
Jiaqi Deng
et al.

Abstract: Background: Exercise has been reported to be associated with a reduced risk of nonalcoholic fatty liver disease (NAFLD), but there is no consensus on the role of weight changes in this association. This study aims to investigate whether the impact of exercise on NAFLD is mainly dependent on weight changes or is inherent to exercise itself.Methods: The study recruited 1671 Chinese NAFLD-free adults in 2019, and collected their exercise habits as well as 3 years of medical examination data including anthropometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Hepatic steatosis is characterized by a dysregulation in lipid metabolism, marked by an excess of fatty acid uptake and de novo lipogenesis (DNL) compared to fatty acid oxidation and export. Previous studies have demonstrated that interventions such as exercise and dietary fiber can attenuate the accumulation of FFA, hepatic TG, and steatosis caused by a high-fat diet. Building upon these findings, our study confirms that obesity induced by a high-fat diet in mice leads to elevated lipid levels in both plasma and liver samples. However, supplementation with KGM significantly attenuated plasma lipid levels as well as hepatic TG and FFA concentrations.…”
Section: Discussionsupporting
confidence: 73%
“…Hepatic steatosis is characterized by a dysregulation in lipid metabolism, marked by an excess of fatty acid uptake and de novo lipogenesis (DNL) compared to fatty acid oxidation and export. Previous studies have demonstrated that interventions such as exercise and dietary fiber can attenuate the accumulation of FFA, hepatic TG, and steatosis caused by a high-fat diet. Building upon these findings, our study confirms that obesity induced by a high-fat diet in mice leads to elevated lipid levels in both plasma and liver samples. However, supplementation with KGM significantly attenuated plasma lipid levels as well as hepatic TG and FFA concentrations.…”
Section: Discussionsupporting
confidence: 73%